Objectively Measuring Acquired Ocular Torsion Secondary to Trochlear Nerve Palsy with Zeiss Cirrus Optical Coherence Tomography. - Borgman, Christopher J. (Optometry & Visual Performance, 2026)
Background: Optical coherence tomography (OCT) allows the identification of key fundus landmarks (fovea and center of optic disc) to help calculate estimated ocular torsion amounts in acquired ocular torsion disorders. A case of chronic trochlear nerve (CN IV) palsy secondary to stroke, in which objective ocular torsion was measured with OCT software and basic trigonometric calculations, follows in this report. Case Report: A 68-year-old female patient with a history of brainstem stroke from five years earlier showed a right-eye hyper deviation of 2?. Resultant Parks-Bielschowsky three-step testing, as well as ocular torsion testing with OCT software measurements, helped determine that the patient's hyper deviation was secondary to a right CN IV palsy. Her objective ocular torsion was calculated using measurement tools and trigonometric functions derived from her OCT scans. Conclusions: OCT technology can provide objective methods for measuring ocular torsion in acquired ocular torsion disorders. Potential OCT software development and future study regarding the use of OCT in these ocular torsion disorders is needed.